(untitled) - McNeill, Daniel (New York, 1993)
General readers who are curious about how a new paradigm is created in basic science will find much of interest in this tight, sharp journalistic treatment of the development of "fuzzy" logic--that is, the mathematics of complexity, which in its more practical applications enables the design of machines that can perform a variety of tasks without detailed human instructions. The authors, both computer writers, chronicle the discipline's beginnings in the early 1960s and the academic battles over its worth that delayed its use in American applied science for years (the Japanese picked it up more quickly), showing how the combined inertia of 20th-century business and science resisted such a major shift in thinking. The mathematicians who created fuzzy logic (and may well regret the playful name they gave it) take center stage here, but the authors' journalistic skills enable them to vividly report on the insular world of high-level research, making the heated debates over fuzzy logic that much more interesting. McNeill/Newbridge Book Club special selection.
Keywords: Automatic control,Computer industry; United states